Pyk2 inhibition promotes contractile differentiation in arterial smooth muscle. Issue 11 (31st March 2017) - Grossi, Mario; Bhattachariya, Anirban; Nordström, Ina; Turczyńska, Karolina M.; Svensson, Daniel; Albinsson, Sebastian; Nilsson, Bengt‐Olof; Hellstrand, Per
Abstract : Modulation from contractile to synthetic phenotype of vascular smooth muscle cells is a central process in disorders involving compromised integrity of the vascular wall. Phenotype modulation has been shown to include transition from voltage‐dependent toward voltage‐independent regulation of the intracellular calcium level, and inhibition of non‐voltage dependent calcium influx contributes to maintenance of the contractile phenotype. One possible mediator of calcium‐dependent signaling is the FAK‐family non‐receptor protein kinase Pyk2, which is activated by a number of stimuli in a calcium‐dependent manner. We used the Pyk2 inhibitor PF‐4594755 and Pyk2 siRNA to investigate the role of Pyk2 in phenotype modulation in rat carotid artery smooth muscle cells and in cultured intact arteries. Pyk2 inhibition promoted the expression of smooth muscle markers at the mRNA and protein levels under stimulation by FBS or PDGF‐BB and counteracted phenotype shift in cultured intact carotid arteries and balloon injury ex vivo . During long‐term (24–96 hr) treatment with PF‐4594755, smooth muscle markers increased before cell proliferation was inhibited, correlating with decreased KLF4 expression and differing from effects of MEK inhibition. The Pyk2 inhibitor reduced Orai1 and preserved SERCA2a expression in carotid artery segments in organ culture, and eliminated the inhibitory effect of PDGF stimulation on L‐type calcium channel and large‐conductance calcium‐activated potassium channel expression in carotid cells. Basal intracellular calcium level, calcium wave activity, and store‐operated calcium influx were reduced after Pyk2 inhibition of growth‐stimulated cells. Pyk2 inhibition may provide an interesting approach for preserving vascular smooth muscle differentiation under pathophysiological conditions. Abstract : The Pyk2 inhibitor PF‐4594755 potently inhibits Pyk2 phosphorylation of vascular smooth muscle cells stimulated by FBS or PDGF‐BB. This is accompanied by increased expression of smooth muscle marker proteins without concomitant effects on cell proliferation. Pyk2 inhibition upregulates SERCA2a expression and may preserve the contractile phenotype by lowering basal intracellular calcium and promoting voltage‐dependent control of calcium influx over the plasma membrane.